Local application of curcumin-loaded nanoparticles as an adjunct to scaling and root planing in periodontitis: Randomized, placebo-controlled, double-blind split-mouth clinical trial - Pérez-Pacheco, Cindy Grace [UNESP]; Fernandes, Natalie Ap. Rodrigues [UNESP]; Primo, Fernando Lucas [UNESP]; Tedesco, Antonio Claudio; Bellile, Emily; Retamal-Valdes, Belen; Feres, Magda; Guimarães-Stabili, Morgana Rodrigues [UNESP]; Rossa, Carlos [UNESP] (Springer Nature, 2021)
Objective: Assess a single local application of curcumin-loaded nanoparticles as an adjunct to scaling and root planing (SRP) in nonsurgical periodontal treatment (NPT). Materials and methods: Twenty healthy subjects with periodontitis received SRP+PLGA/PLA nanoparticles loaded with 50 μg of curcumin (N-Curc) or SRP+empty nanoparticles. Probing pocket depth (PPD), clinical attachment level (CAL), and bleeding on probing (BOP) were monitored at baseline, 30, 90, and 180 days. IL-1α, IL-6, TNFα, and IL-10 in the gingival crevicular fluid (GCF) were assessed by ELISA, and counts of 40 bacterial species were determined by DNA hybridization at baseline, 3, 7, and 15 days post-therapy. Results: PPD, CAL, and BOP were similarly and significantly improved in both experimental groups. There was no difference in GCF cytokine levels between experimental groups, although IL-6 was decreased at 3 days only in the N-Curc group. NPT reduced counts of red complex bacterial species in both groups. Veillonella Parvula counts increased significantly only in N-Curc group at 7 days, whereas Aggregatibacter actinomycetemcomitans counts increased significantly only in the control group from day 3 to day 15. Conclusion: We conclude that a single local administration of nanoencapsulated curcumin in periodontally diseased sites had no additive benefits to NPT. Clinical relevance: Our results showed that a single local application of curcumin-loaded nanoparticles associated with nonsurgical periodontal therapy did not improve clinical outcomes. Hence, our findings do not support the use of curcumin as an adjunct to nonsurgical periodontal therapy.
Keywords: Curcumin; Dental Scaling; Nanoparticles; Periodontitis